Magnetometer transducer based on oscillistor effect - A. I. Cheredov; A. V. Shchelkanov (Омский научный вестник)
Magnetic testing is one of the most widespread types of the NDT. When carrying out magnetic testing various analog magnetic measuring sensors are used: ferroprobe, based on Gauss and Hall effects, etc. A perspective direction of research in the field of nondestructive testing and technical diagnostics is the development of measuring transducers with a digital output signal, or a signal easily convertible into a code. The paper considers magnetic transducer based on the oscillistor effect, which has a threshold nature and involves the appearance of electric current oscillations, flowing through a semiconductor sample, placed in the longitudinal electric and magnetic fields. The results of experimental studies of the dependence of the threshold electric field strength on the magnetic field strength are presented. The scheme of the converter of magnetic field induction into the impulses of electric voltage, and diagrams of its work are given. The sensitivity of the converter depends on the frequency of the sample frequency generator and the conversion coefficient of the ramp generator.